Risk management model in sharia pawnbroking business solusi emas syariah pt bank danamon tbk. - Ardiansyah, Dhany; R. Jayaprawira, Acep (The Indonesian Journal of Business Administration, 2016)
Abstract - In the Indonesian banking business, pawnbroking is one of the most prospecting financing business thatÂ  has not been touched by conventional bank, and it is only sharia banking that may run this pawnbroking business. Under sharia principle, the agreement / akad has been ruled by National Sharia Council (Dewan Syariah Nasional) where the basis of transaction is through Akad Rahn & Qardh, however, accepted pawn collateral is limited to gold only. For period 2010 to 2014, majority of sharia banks have run pawnbroking business, such as Bank Syariah Mandiri, BRI Syariah, BNI Syariah, BTPN Syariah, BJB Syariah, CIMB Niaga Syariah, dan Danamon Syariah. Nevertheless, risk management of pawnbroking business is not easy, where the potential risks always happen and occur, not only those small amount of risks with high frequencies, but also low frequency with significant financial impact, or even high amount of potential risks with high frequencies. With respect to the complexity of risk management and the slow business performance and achievement, majority of the above sharia banksâ€™ managements have decided to stop the product and no more selling to its customers. The â€œstop-pawn productâ€ decision had happened during 2013-2014. Bank Danamon Syariahâ€™s management has decided to totally stop selling pawn product as per 15 April 2015. This research is solely purposed for exploration and management of the risks spread out in the pawnbroking process flow, and those are analyzed based on Basel 2 Accord and Peraturan Bank Indonesia related to risk management, and creating the most effective and efficient risk management model for pawnbroking. The choice of Bank Danamon Syariah as the research base because of this bank is the only sharia bank window who has opened 150 branches whose services are uniqely focused on sharia pawnbroking, and operated since 2010 until 15 April 2015. Â Keywords: sharia 7 key pawnbroking process, risk management model, risk identification, risk level, risk mapping, risk mitigation. Â